(untitled) (Anwer Khan Modern Medical College Journal, 2011)
Obesity is a major public health problem which is not only confined to developed countries but has now become an important public health problem in developing countries like Bangladesh also. High calorie intake in diet due to increased consumption of refined sugars, sweetened beverages, vegetable oils, chunk and fast food and lack of physical activity, absence of play ground (open-spaces), sedantery life style all play a role in the development of obesity. Excess adiposity also known as obesity and excess body weight are associated with increased association with different types of diseases like type 2 diabetes, dyslipidemias, cardiovascular disease, hypertension and cancer. This review article highlights the pathogenesis, disease association with obesity. Key words: Obesity; Disease Association; Public Health Problem DOI: 10.3329/akmmcj.v1i2.7461 Anwer Khan Modern Medical College Journal 2010; 1(2): 21-24